Phenomenological investigation of a carbon fibre based strain sensor with spatial resolution by means of time domain reflectometry: Phänomenologische Untersuchung eines Dehnungssensors basierend auf Kohlenstofffasern zur ortsaufgelösten Messung mittels elektrischer Zeitbereichsreflektometrie. Issue 11 (11th November 2016) - Höhne, R.; Ehrig, T.; Kostka, P.; Modler, N.
Abstract : Fibre reinforced plastics feature versatile function‐integrative capabilities, e.g. the possibility to realise embedded Structural Health Monitoring (SHM) systems. Material‐compatible sensors are a prerequisite for a robust and reliable function of such systems. Among others, sensors based on carbon fibres are in the focal point of research due to their high material compatibility. The contribution proposes a novel continuous strain sensor based on embedded carbon fibres. In opposition to typical carbon fibre sensors, the presented measurement principle is based on the reversible opening and closing of aligned carbon fibre fragments. The phenomenological effects are investigated by a combined electrical, mechanical and optical analysis. The sensor features a strain sensitivity that is up to four orders of magnitude higher than the one of current carbon fibre sensors. For the first time, the application of the electrical time domain reflectometry for a spatially resolved strain measurement with carbon fibre sensors is presented here. In addition a damage localisation capability with an observed spatial resolution in the lower mm‐range is possible.